A review of simple to scientific models for anaerobic digestion - Kythreotou, Nicoletta; Florides, Georgios A.; Tassou, Savvas A. (My University, 2014)
To fully model the anaerobic digestion process, biological and physico-chemical background, the kinetics of bacterial growth, substrate degradation and product formation have to be taken into account. The presented approaches differ depending on the requirements and the developer of the model. Important parameters affecting the process such as temperature, which can cause great inaccuracy, are rarely included in the models. Simple calculators are also available that estimate the applicability of the process to a specific farm and provide information to a farmer or a decision maker. Six simple calculators are presented in this study: AD decision support software, Anaerobic Digestion Economic Assessment Tool, BEAT2, BioGC, FarmWare and GasTheo. The simpler calculators mainly use the relation that exists between volatile solids and biogas production. A tested case of 100 dairy cows and 50 sows was applied to the simple calculators to compare the results.
Keywords: Anaerobic digestion; Biogas production; Modelling; Simple calculators